Love and the silver lining [large type] - Gray, Tammy L. (A state of grace novel, 2021)
"Darcy Malone's dreams of mission work are dashed on her eve of fulfilling them: The Guatemalan school she was to teach at has closed. Devastated because she's already quit her job and given up her apartment, she also loses the perfect escape from the aftermath of her parents' divorce. Stuck in her worst-case scenario, Darcy takes an unexpected offer to move in with Bryson Katsaros's little sister, despite the years of distrust that's grown between her and Bryson, the lead singer in her best friend Cameron's band. As she meets those close to him, Darcy realizes that Bryson is more than she believed. Struck with the need to find a purpose, Darcy jumps at the chance to care for and train a group of dogs, with the aim of finding each a home before their bereaved owner returns them to animal control. But it's Darcy herself who will encounter a surprising rescue in the form of unexpected love, forgiveness, and the power of letting go"--